ANALISIS TERHADAP RUMAH YANG TERIKAT JUAL-BELI YANG DIJAMINKAN KE BANK SECARA SEPIHAK (STUDI KASUS PUTUSAN PN JAKARTA BARAT NOMOR 339/Pdt.G/2018/PN.Jkt.Brt.) - Vindy Kusuma; Mia Hadiati (Jurnal Hukum Adigama, 2022)
Society utilize the land as a place to do business and place to live which it means a house. House canbe obtained from buy and sell transaction upon the agreement of the parties. Problems can be found intransaction process as in the case of West Jakarta District Court Decision Number339/Pdt.G/2018/PN.Jkt.Brt. regarding the seller committing an unlawful act by pledging a housecertificate bound by a sale-purchase agreement without buyer permission. The problem are how is thestatus of the buyer ownership rights of the house that is pledged to the bank without buyer permissionand how is the buyer legal protection for the house that is guaranteed to the bank without the buyerpermission. The research method using legal research normative data supported by interviews. Theresearch result shows the buyer is not the owner of the house because the process of transferringownership has not been carried out and the certificate is still listed as the name of the seller, but it’s theright of the buyer to have the house, because the buyer has done his obligations to pay the price housein installments, so the house cannot be guaranteed by the bank. Buyer don’t get legal protectionbecause the buyer lost in court. Buyer must file a re-suit to the court by providing a legal basis andwithdraw the parties involved in the case with the aim of providing arguments for the lawsuit in thecourt.